2021
DOI: 10.1177/0972262920987326
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Boardroom Challenge, Board Effectiveness and Corporate Stewardship During COVID-19

Abstract: The global COVID-19 pandemic has led to spawning norms in all quarters, including the corporate boardrooms. The transformation required in boards is unprecedented in its intensity to overcome the changing challenges in the global market. A conceptual note has been developed to understand the boardroom challenges and the requirement of corporate stewards to combat the situation of health crises. The article discusses the new boardroom challenges the organization have to face such as virtual boardroom, right boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Trust in the company can also be obtained by improving ESG performance. According to Kaur et al (2021), good stewardship behaviour helps companies to adapt to the external economic environment and create shareholder value. With the external economic environment having changed drastically because of the COVID‐19 pandemic, companies can adapt and overcome these changes with stewardship behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust in the company can also be obtained by improving ESG performance. According to Kaur et al (2021), good stewardship behaviour helps companies to adapt to the external economic environment and create shareholder value. With the external economic environment having changed drastically because of the COVID‐19 pandemic, companies can adapt and overcome these changes with stewardship behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Koutoupis, et al [7] reviewed related literature on corporate governance, environmental and social governance and corporate social responsibility during the pandemic, revealing that most previous studies on corporate governance during the pandemic are theoretically based due to insufficient accounting data yielding an inconclusive result and suggested further empirically based studies on corporate governance and the pandemic for better clarification. In addition, Kaur, et al [29] examined the new boardroom challenges posed by the pandemic outbreak, such as virtual boardrooms, IT governance, threats to continuity and sustainability and dynamic and systematic risk management revealing that the introduction of virtual board meetings, quick responses and board effectiveness from companies' managers helped to sustain companies during the pandemic. Jin, et al [30] empirically examined corporate governance structure and performance in the tourism industry during the pandemic and revealed that the pandemic had a greater impact on the performance of tourism companies than other industries.…”
Section: Prior Studies On the Covid -19 Pandemic Corporate Governance...mentioning
confidence: 99%
“…These put constraints on meetings and on many normal managerial activities and can also hamper the effectiveness of internal control mechanisms. This poses many challenges to governance, as according to theories of tunnelling, periods of great uncertainty and tumult create opportunities for insiders to extract private rents at the expense of other stakeholders (Kaur et al , 2021). According to Deloitte (2021), an effective BoD response to business disruption resulting from the pandemic includes the following: management’s risk assessments in the midst of COVID-19; business continuity plans; organisational resilience; development of new digital strategies; enabling of the digital workforce; and communication plans with both internal and external stakeholders. …”
Section: Literature Reviewmentioning
confidence: 99%